2009
DOI: 10.1007/s10530-009-9464-x
|View full text |Cite
|
Sign up to set email alerts
|

Offspring genetic structure reveals mating and nest infestation behaviour of an invasive parasitic fly (Philornis downsi) of Galápagos birds

Abstract: The natural reproductive behaviour of invasive insects is pivotal knowledge for managing species of ecological or economic concern. We use microsatellites to examine female multiple mating and multiple nest infestations in the introduced parasitic fly, Philornis downsi, which causes high mortality in endemic birds on the Galápagos Islands. We analyse larvae and pupae within 57 nests from Santa Cruz and Floreana Islands in both the highland and lowland habitats. Sib-ship reconstructions of offspring revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Bennett and Whitworth (1991b), in an experimental study with adult flies of the genus Protocaliphora, found that adult flies do not move large distances and that new infestations occur ,50 m from where adults emerged. Dudaniec et al (2010) also found lower levels of genetic relatedness in P. downsi when nests where located in more arid environments and host nesting density was lower. Open areas of grasslands that separate patches of forest may act as barriers for botfly dispersal.…”
Section: Discussionmentioning
confidence: 73%
“…Bennett and Whitworth (1991b), in an experimental study with adult flies of the genus Protocaliphora, found that adult flies do not move large distances and that new infestations occur ,50 m from where adults emerged. Dudaniec et al (2010) also found lower levels of genetic relatedness in P. downsi when nests where located in more arid environments and host nesting density was lower. Open areas of grasslands that separate patches of forest may act as barriers for botfly dispersal.…”
Section: Discussionmentioning
confidence: 73%
“…5) Flies entered the nest even though chicks were already parasitized and there were numerous fly larvae and eggs already present in the nest. Nest infestation by multiple P. downsi females has been confirmed by microsatellite studies (Dudaniec et al 2010); however, to our knowledge, this is the first record of a P. downsi female visiting a nest with a known number of conspecific larvae and eggs. 6) Early-instar P. downsi larvae can affect other areas of the heads of the chicks in addition to the nostrils, beak, and ears , suggesting subcutaneous habits (M. Quiroga pers.…”
mentioning
confidence: 61%
“…As P. downsi intensity increases with nestling age [40], this could bias the data. Thus, we analysed nests with chicks of 6 days and younger separately to reduce the effect of nestling age.…”
Section: Resultsmentioning
confidence: 99%